Coagulation- and fibrinolysis-related genes for predicting survival and immunotherapy efficacy in colorectal cancer - Ma, Yanling; Wang, Bofang; He, Puyi; Qi, Wenbo; Xiang, Ling; Maswikiti, Ewetse Paul; Chen, Hao (Frontiers in Immunology, 2022)
Background Colorectal cancer (CRC) is a common cancer and has a poor prognosis. The coagulation and fibrinolysis system are closely related to the progression of malignant tumors, and is also related to the immunotherapy of malignant tumors. Herein, we tried to predict survival and immunotherapy effect for patients with CRC using a novel potential prognostic model. Methods Through online data of TCGA and GEO, we screened significantly DEGs to construct a prognostic model, followed by obtaining immune-related genes (IRGs) from the ImmPort database and coagulation and fibrinolysis related genes（CFRGs）from the Genecards database. The predictive power of the model is assessed by Kaplan–Meier survival curves as well as time-dependent ROC curve. Moreover, univariate and multivariate analyses were conducted for OS using Cox regression models and build the nomogram prognostic model. In the end we further studied the possibility that CXCL8 was associated with immunocytes infiltration or immunotherapy effect and identified it by Immunohistochemistry and Western blot. Results Five differentially expressed genes (DEGs) (CXCL8, MMP12, GDF15, SPP1, and NR3C2) were identified as being prognostic for CRC and were selected to establish the prognostic model. Expression of these genes was confirmed in CRC samples using RT-qPCR. Notably, those selected genes both are CFRGs and IRGs can accurately predict the OS of CRC patients. Furthermore, CXCL8 is highly correlated with tumor microenvironment and immunotherapy response in CRC. Conclusion Overall, our established IRGPI can predict very accurately the OS of CRC patients. CXCL8 reflect the immune microenvironment and reveal the correlation with immune checkpoints among CRC patients.